Purifying the Heart, Unveiling the Truth: Understanding Al-Ghazālī's Epistemology - Husni, Amin Said; Bahar, Moh. Syaeful; Harnadi, Dodik (Journal of Pesantren and Diniyah Studies, 2025)
Al-Ghazālī is one of the foremost thinkers in the tradition of Islamic thought. His life story has inspired many historians worldwide to document his journey. His interdisciplinary thinking has given rise to numerous works that explore his contributions from various scholarly perspectives. Although his ideas culminated in a philosophical product that diverged from the tradition of earlier philosophers, Al-Ghazālī could not entirely avoid employing philosophical logic in developing a philosophy of knowledge oriented towards unveiling the ultimate truth. This paper seeks to uncover Al-Ghazālī's philosophy of knowledge, particularly within the ontology and epistemology he developed. His philosophy of knowledge is rooted in a theological affirmation of God's oneness. Building upon this ontological foundation, Al-Ghazālī posits a single source of knowledge. Consequently, he opposes the compartmentalization of knowledge into distinct categories. Moreover, since knowledge emanates from the true substance of God, it attains a noble status in Al-Ghazālī's understanding. For Al-Ghazālī, authentic knowledge is what he terms al-ilmu al-yaqini, which can only be achieved through the illumination of the heart or mukasyafah. His concept of al-ilmu al-yaqini arises from his belief that the purpose of his scholarly journey is to uncover the substance of all realities or haqaiq al-umur. His epistemological perspective is characterized by a strong monism, emphasizing that all knowledge ultimately derives from and leads back to the singular divine source.